Analysis of Educational Policy in the Framework of Learning Efficiency and Effectiveness - Mahrus, Mahrus; Karimullah, Suud Sarim (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2022)
This study aims to reveal how the policy-making process carried out by SMPS-IT and SMAS-IT Muslimah Sejati Bekasi, starting from the formulation, and implementation, to policy evaluation, which will end in the value of effectiveness and efficiency as a form of institution existence. This study uses qualitative research through descriptive analysis methods with data collection models using interviews, documentation, observations, and triangulation of sources, techniques, and theories. Through this method, researchers get a finding containing policy cases from two institutions related to the similarities and differences between the formulation process and effectiveness and efficiency. In the formulation process, both have different policies between online and offline, but in the formulation, each has weaknesses consisting of flaws in analysis and alternatives. Meanwhile, in terms of implementation, there are obstacles, individually and institutionally, composed of weak motivation and the disintegration of some teachers and staff. The evaluation has similarities in the implementation system, namely, using a formative, summative model. In terms of effectiveness and efficiency, both achieved the same value. Namely, they were both able to graduate students of 30 Juz Qur'an, while inefficiency there were shortcomings in financing and dependence on electricity in the teaching and learning process.